ANALYSIS OF BEHAVIORAL FACTORS AND LEVEL OF ANXIETY OF SCHOOLCHILDREN IN THE CONDITIONS OF THE RUSSIAN-UKRAINIAN WAR - V. Zhdan; I. Holovanova; Sh. Wang; N. Obrevko; O. Korneta; I. Bіelikova; I. Kaidashev; U. Haque; M. Khorosh; I. Popovich (Проблеми екології та медицини)
Background. The mental health of Ukrainian children is of great concern. The current study aims to investigate the behavioral factors and level of anxiety of schoolchildren aged 11-17 years old in Kremenchuk in the conditions of war. Method: A total of 114 children took part in the survey in 2022. In addition, a total of 156 children filled out questionnaires on behavioral factors in 2021, and 114 children filled out questionnaires on behavioral factors in 2022. Of note, children’s questionnaires were available to their parents, who were able to correct children’s answers on the state of health and lifestyle. The level of situational and personal anxiety, and the dynamics of behavioral factors of students were assessed. The scale of personal and situational anxiety by Spielberger and Khanina was used to assess situational and personal anxiety. Result. The mean age of the respondents in 2021 was 13.8±1.7 years (max = 17; min = 11), with 78 (68.4%) women and 36 (31.6%) men. In addition, 20 (17.5%) participants were internally displaced persons. Of note, internally displaced persons (IDPs) had a 5.4 times greater chance of situational anxiety than the local schoolchildren (odds ratio, OR=5.4, 95% confidence interval, CI: 1.66-9.39, p=0.045). Additionally, the level of personal anxiety in women is 6.6 times higher than in men (OR=6.66, 95% CI: 2.79-15.92, p =0.028). Furthermore, eating junk food was associated with higher odds of situational anxiety in war conditions (OR=3.11, 95% CI: 1.37-7.03, p=0.035). Conclusion. The mental health and sleep health among children living in Kremenchuk are worrisome. The current study indicates the high psychological burden on Ukrainian children, especially IDPs. Constant mental health care during the initial period of resettlement is urgently needed.